Violence fondatrice, mémoires de la dictature et politiques de la reconnaissance - Ricardo Salas Astrain (Appareil)
This article develops a philosophical thesis about violence foundational American political process, and therefore is not a direct pose about the military dictatorship, in other words, we propose a general hypothesis about the “founding violence” formed societies in Latin America, and determines much force facts that occurred in those hard 17 years experienced by the Chilean society and many more in other Latin American versions. This background can understand from a historical phenomenology resulting violence and cruelty of the Chilean dictatorship. The main idea behind is that the 1973 military coup is not a random violent act or a new phenomenon, but it is part of an ongoing “logic of negation” present in Chilean society, which has marked the space-time of sociability ours, and therefore refers both to a question connected with memory both long and short duration as the reparation of victims that is part of a politics of recognition. Thus, it is necessary to propose a philosophical view of the founding of political violence, as opposed to the political.